Students’ Perception of Lexical Errors and the Teachers’ Feedback Long- term Effects - Budianto, Suhartawan (Dinamika : Jurnal Sastra dan Budaya, 2017)
The errors of L2 learners are much influenced by their L1. they (errors) were the result of interference in the learning of a second language from the habits of the first language.Corrective Feedback (CF) does not always provide the correct form but it also forces learners to utilize their own resources in constructing a reformulation.Direct feedbacks do not figure out the actual performance of students’ comprehension in correcting the errors because teachers have provided the correct one. Teachers have to invite students to be active finding the correct one from their errors they produce